Role of cardiovascular magnetic resonance in the prognosis of patients with myocardial infarction with non-obstructive coronary arteries - Nuria Vicente-Ibarra; Eloisa Feliu; Vicente Bertomeu-Martínez; Pedro Cano-Vivar; Pilar Carrillo-Sáez; Pedro Morillas; Juan Miguel Ruiz-Nodar (Journal of Cardiovascular Magnetic Resonance, 2021)
Abstract Background It is estimated that 5% to 10% of patients with myocardial infarction (MI) present with no obstructive coronary artery lesions. Until now, most studies have focused on acute coronary syndrome, including different clinical entities with a similar presentation encompassed under the term MINOCA (MI with non-obstructive coronary arteries). The aim of this study is to assess the prognosis of patients diagnosed with true infarction, confirmed by cardiovascular magnetic resonance (CMR), in the absence of significant coronary lesions. Methods Prospective multicenter registry study, including 120 consecutive patients with a CMR-confirmed MI without obstructive coronary artery lesions. The primary clinical outcome was major adverse cardiovascular events (MACE: death, non-fatal infarction, stroke, or cardiac readmission), assessed over three years. Results Seventy-six patients (63.3%) were admitted with a diagnosis of acute coronary syndrome, and 44 (36.6%) for other causes (mainly heart failure); the definitive diagnosis was established by CMR. Most patients (64.2%) were men, and the mean age was 58.8 ± 13.5 years. Patients presented with small infarcts: 83 (69.1%) showed late gadolinium enhancement (LGE) in one or two myocardial segments, mainly transmural (in 77.5% of patients) and with a preserved left ventricular ejection fraction (median 54.8%, interquartile range 37–62). The most frequent infarct location was inferolateral (n = 38, 31.7%). During follow-up, 43 patients (35.8%) experienced a MACE, including 9 (7.5%) who died. In multivariable analysis, LGE in two versus one myocardial segment doubled the risk of adverse cardiac events (hazard ratio [HR] 2.32, 95% confidence interval [CI] 0.97–5.83, p = 0.058). Involvement of three or more myocardial segments almost tripled the risk (HR 2.71, 95% CI 1.04–7.04, p = 0.040 respectively). Conclusions Patients with true MI but without significant coronary artery lesions predominantly had small infarcts. Myocardial 3-segment LGE involvement is associated with a significantly higher risk of adverse cardiac events.